Characterization and rheological behaviour analysis of the succinoglycan produced by Rhizobium radiobacter strain CAS from curd sample. (March 2017) - Andhare, Prasad; Delattre, Cédric; Pierre, Guillaume; Michaud, Philippe; Pathak, Hilor
Abstract: An exopolysaccharide (EPS) producing strain CAS grown in a Bushnell Haas medium was isolated from curd sample and identified as Rhizobium radiobacter CAS. The biopolymer was duly characterized by FT-IR and NMR spectroscopy and was found to be composed of glucose and galactose in a molar ratio of 6.99:1 as confirmed by HPAEC; thus depicting it to be succinoglycan type exopolysaccharide. In addition, conceivable presence of one succinate and two acetate groups of succinoglycan was estimated using 1 H NMR analysis by specific signal integration. Furthermore, as a documented fact, the insights into the rheological behaviors portray phenomenal influences in food, cosmetics and pharmaceutical industries as thickening, gelling, stabilizing and emulsifying agent. However, this piece of information has remained unnoticed from the existing literature. Thus, in the present study the rheological properties of succinoglycan type biopolymer in aqueous solution were systematically investigated. The flow behaviour testing in an aqueous solution verified its pseudoplastic character and higher apparent viscosity. Furthermore, study on its potential strength and tolerance in various thermal conditions, cation salts, and pH has been studied in depth. Such a study can provide a thorough guidance on the rheological behaviour of the biomaterial and thus impart significant insights into postulating its application spectrum into food, cosmetics and pharmaceutical industrial sectors. The present study is thus, one of its kinds which decipher the complete rheological behavioural portrait. Graphical abstract: Highlights: Exopolysaccharide producing isolate identified as Rhizobium radiobacter CAS. HPAEC showed that EPS was a succinoglycan type biopolymer composed of glucose and galactose with molar ratio 6.99:1. FT-IR and 1 H NMR spectra showed presence of one succinate and two acetate groups of succinoglycan. Stable under wide range pH, temperature and ionic strength. Possible candidate for food industries.